Integrasi Sistem Informasi Manajemen Sdm Dalam Transformasi Digital: Pengaruh Terhadap Efisiensi Operasional: (Studi Pada Industri Manufaktur di Cilegon) - Supriyadi (LPPM STIE Bisnis Internasional Indonesia, 2024)
This study aims to evaluate the impact of integrating Human Resource Management Information Systems (HRMIS) on organisational operational efficiency in the context of digital transformation. A quantitative approach with a survey design was used to collect data from 20 organizations that have implemented HRMIS in Indonesia. Linear regression analysis showed a positive and significant relationship between the level of HRMIS integration and operational efficiency, with a regression coefficient of 0.38 and an R-squared of 0.65. Additionally, t-tests and F-tests indicated that the regression model is statistically significant, with p-values of 0.0001 and 0.00001, respectively. The correlation between the level of HRMIS integration and operational efficiency also indicated a strong relationship, with a correlation coefficient of 0.81. These findings suggest that HRMIS integration significantly contributes to improving operational efficiency, with perceived benefits including time savings, increased data accuracy, and enhanced decision-making capabilities. Although organizations face challenges in integrating HRMIS, such as resistance to change and interoperability issues, the benefits obtained indicate that investment in this technology can provide significant returns. This study provides important contributions to the literature on digital transformation and HR management and offers practical guidance for HR managers in optimizing HRMIS use in the digital era. It is hoped that the results of this study will encourage more organizations to adopt and integrate HRMIS, thereby improving their operational efficiency and competitiveness in the global market.